PENERAPAN MEDIA PEMBELAJARAN PAPAN PERKALIAN UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN MATEMATIKA DI KELAS III SD NEGERI 98 SAILONG KABUPATEN BONE - Nur Aini; Akhmad Syahid; Martini; Abdul Wahab; Muh. Aidil Sudarmono R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the process of implementing multiplication board learning media and test its effectiveness in improving mathematics learning outcomes of third-grade students at SD Negeri 98 Sailong, Bone Regency. This study was motivated by the low learning outcomes of students in multiplication material, so that learning innovations are needed that can help students understand the concept of multiplication easily. The study used a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model which was carried out in two cycles with 8 subjects. Data collection techniques consisted of observation, interviews, tests, and documentation. The study was carried out through the stages of planning, action implementation, observation, and reflection. The results showed a significant increase in student learning outcomes. In the pre-cycle stage, learning completeness was 25% (average 40). increased to 50% (average 63.75) in cycle I, and reached 100% (average 93.75) in cycle II. Thus, it can be concluded that the application of multiplication board media is effective in improving mathematics learning outcomes of third-grade students at SD Negeri 98 Sailong, Bone Regency.